Functional Quality and Radical Scavenging Activity of Selected Watermelon (Citrullus lanatus (Thunb.) Mansfeld) Genotypes as Affected by Early and Full Cropping Seasons - Imen Tlili; Riadh Ilahy; Leila Romdhane; Thouraya R’him; Hatem Ben Mohamed; Hatem Zgallai; Zouhair Rached; Muhammad Azam; Imen Henane; Mohamed Najib Saïdi; Zoltàn Pék; Hussein G. Daood; et al. (Plants, 2023)
Growing conditions and seasonal fluctuations are critical factors affecting fruit and vegetable nutritional quality. The effects of two partially overlapping cropping seasons, early (ECS; January–May) and full (FCS; March–July), on the main carpometric traits and bioactive components of different watermelon fruits were investigated in the open field. Four watermelon genotypes, comprising of three commercial cultivars ‘Crimson Sweet’, ‘Dumara’, ‘Giza’, and the novel hybrid ‘P503 F1’, were compared. The carpometric traits varied significantly between genotypes. Soluble solids and yield were higher under FCS than ECS. The variation affecting colour indexes between the two growing seasons exhibited a genotype-dependent trend. The antioxidant components and radical scavenging activity of watermelon fruits were also significantly affected by differences in received solar energy and temperature fluctuations during the trial period. The average citrulline, total phenolics and flavonoid contents were 93%, 71% and 40% higher in FCS than in ECS. A genotype-dependent variation trend was also observed for lycopene and total vitamin C between cropping seasons. The hydrophilic and lipophilic radical scavenging activities of the pulp of ripe watermelon fruits of the different genotypes investigated varied between 243.16 and 425.31 µmol Trolox Equivalent (TE) of 100 g−1 of fresh weight (fw) and from 232.71 to 341.67 µmol TE of 100 g−1 fw in FCS and ECS, respectively. Our results, although preliminary, show that the functional quality of watermelon fruits is drastically altered depending on the environmental conditions that characterize the ECS and LCS.